A comparative Study of Novel Extramedullary Fixation and Dynamic Hip Screw in the Fixation of Intertrochanteric Fracture: A Finite-Element Analysis - Ding, Kai; Zhu, Yanbin; Wang, Haicheng; Li, Yonglong; Yang, Weijie; Cheng, Xiaodong; Zhang, Yingze; Chen, Wei; Zhang, Qi (Frontiers in Surgery, 2022)
Background: Dynamic hip screw (DHS) was one of the most widely internal fixations for stabilizing intertrochanteric fracture, however, with a high risk of post-operative complications. The triangle support fixation plate (TSFP) was developed to reduce the postoperative complications and the purpose of study was to evaluate biomechanical performance of DHS and TSFP, and demonstrate the rationality of triangular internal fixation for stabilizing intertrochanteric fractures. Methods: The CT data of proximal femur was used to establish finite element models. Evans type Ⅰ and Ⅳ intertrochanteric fracture were constructed and stabilized with DHS and TSFP. The Von-Mises stress, maximum principal stress, minimum principal stress and displacement were used to evaluate the biomechanical effect of two implants on intertrochanteric fracture. Results: Under 600N axial load, the maximum stress and displacement of intact proximal femur was 13.78MPa and 1.33mm, respectively. The peak stress of bone in TSFP was 35.41 MPa and 68.97 MPa for treating Evans type Ⅰ and Ⅳ intertrochanteric fracture, respectively, which was lower than those in DHS. The maximum overall displacement and relative distance of fracture surface in DHS fixation model were 1.66mm and 0.10 mm for treating Evans type Ⅰ intertrochanteric fracture which was 29.59% and 150% higher than that in TSFP, and were 2.24mm and 0.75mm for treating Evans type Ⅳ intertrochanteric fracture which was 42.58% and 650% higher than that in TSFP. Conclusions：In conclusion, TSFP has obvious advantages in stress distribution and stability than DHS, providing a promising option for treatment of intertrochanteric fractures.